Barriers and drivers to COVID-19 protective behaviours of forcibly displaced myanmar nationals (FDMN)/ rohingya refugees in Cox's bazar, Bangladesh: A scoping review - Sarah Reda; Zarah Yusuf; Basel Karo; Balwinder Singh Chawla; Andreas Jansen; Saskia Lange; Jorge Martinez; Emily Dorothee Meyer; Julia Neufeind; Aarti Shrikrishana Singh; Elisa Wulkotte; Cath Jackson (Journal of Migration and Health, 2025)
About 900.000 Forcibly Displaced Myanmar Nationals (FDMN)/ Rohingya refugees live in makeshift camps in Cox's Bazar, Bangladesh. During the COVID-19 pandemic, protective behaviors were particularly important in this setting of previous severe infectious disease outbreaks. To identify barriers, drivers and interventions for those behaviors, a scoping review of MEDLINE, Embase, Web of Science, Global Health and grey literature was conducted in October 2021 and updated in June 2024. The modified Capability-Opportunity-Motivation-Behavior (COM-B) framework and Behavior Change Wheel were used to organize available evidence. A total of 4014 (3654 in 2021, 360 in 2024) records were reviewed and 51 (38 in 2021, 13 in 2024) articles included. Articles reported on protective behaviors (as a general concept), handwashing, social distancing, isolation/quarantine, mask wearing, testing, treatment and vaccination. Barriers and drivers to these behaviors spanned all four COM factors reflecting both individual and environmental influences. Most frequently cited barriers and drivers were found in the motivation (e.g. belief, fear, trust) and physical opportunity (e.g. information, the physical camp environment) factors. Gaps in the evidence were views of health service providers, and differences between camps and population groups. Most interventions focused on information, education or training (e.g. campaigns, community engagement) and environmental restructuring (e.g. increased provision of WASH facilities, COVID-19 isolation and treatment centres). Most articles reported recommendations for interventions. There was some evidence of implementation but little evaluation. This review identified complex and inter-related barriers and drivers to COVID-19 protective behaviors in Cox's Bazar, and many interventions to address these. Addressing the above-mentioned evidence gaps would assist future development of effective targeted interventions, tailored to the needs of specific population groups.